2017
DOI: 10.3390/molecules22111863
|View full text |Cite
|
Sign up to set email alerts
|

Benzoic Acid Derivatives with Trypanocidal Activity: Enzymatic Analysis and Molecular Docking Studies toward Trans-Sialidase

Abstract: Chagas, or American trypanosomiasis, remains an important public health problem in developing countries. In the last decade, trans-sialidase has become a pharmacological target for new anti-Chagas drugs. In this work, the aims were to design and find a new series of benzoic acid derivatives as trans-sialidase (TS) inhibitors and anti-trypanosomal agents. Three compounds (14, 18, and 19) sharing a para-aminobenzoic acid moiety showed more potent trypanocidal activity than the commercially available drugs nifurt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…The validated drugs in this study were potently effective against the trypomastigote but not the epimastigote form. This behavior can be explained by the morphological differences between the two stages of T. cruzi and has already been observed in previous studies [ 96 , 97 , 98 ]…”
Section: Discussionsupporting
confidence: 76%
“…The validated drugs in this study were potently effective against the trypomastigote but not the epimastigote form. This behavior can be explained by the morphological differences between the two stages of T. cruzi and has already been observed in previous studies [ 96 , 97 , 98 ]…”
Section: Discussionsupporting
confidence: 76%
“…When computational strategies screened more than 3000 drugs approved by the Food and Drug Administration (FDA), and in vitro and in vivo tests were performed, it was seen that the anti-inflammatory sulfasalazine ( Figure 1F ) can be used as a lead to design new enzyme inhibitor drugs (Lara-Ramirez et al, 2017). Recently, it was found that molecules containing amide, hydroxyl, and carboxylic acid radicals in their aromatic rings can enhance the biological activity of these enzyme inhibitors, which may lead to a better rational drug design (Kashif et al, 2017).…”
Section: Synthetic Drugs and New Therapeutic Approaches For Chagas DImentioning
confidence: 99%
“…Benzoic acid and its derivatives have shown antibacterial activity and assisted in the removal of exfoliated cells. Discovered to be eligible for Chagas disease treatment through different biological mechanism and also show significant trypanocidal activity [5]. Reaction involving isatoic anhydride, amine and benzyl E.E.…”
Section: Introductionmentioning
confidence: 99%